Electronic Nursing Records: Importance for Nursing and Benefits of Implementation in Health Information Systems—A Scoping Review - Daniela Ivova Taneva; Vasilka Todorova Gyurova-Kancheva; Angelina Georgieva Kirkova-Bogdanova; Diana Angelova Paskaleva; Yovka Tinkova Zlatanova (Nursing Reports)
Introduction: The advancement of nursing science and practice necessitates the documentation of information, which is increasingly being recorded in electronic mediums due to the progress of information technology. Various countries around the world have implemented electronic nursing records (ENRs) or are in the process of implementing them. This study aims to ascertain the significance of electronic nursing records and consolidate their primary benefits for nursing. Methods: The study utilized an established scoping review methodology (Arksey and O‘Malley protocol; JBI method; PRISMA ScR (2018)). Results: Out of 6970 initial articles extracted from four databases, 36 were included in the study. Several essential elements for structuring, introducing, and emphasizing the importance of ENRs have been recognized, including the availability of standardized terminology, enhancement of nursing care quality, advancement of research activity, integration with electronic systems, optimization of healthcare, and conditions for ENR integration. Conclusions: Electronic nursing records are indispensable and beneficial for enhancing care quality, improving patient safety, and affirming the autonomy of the nursing profession.